Avaliação comparativa da atividade antioxidante de Artemisia annua, artemisinina e artemeter administrados via oral em tilápias do nilo, Oreochromis niloticus: estudos in vivo e pós-abate - Aracati, Mayumi Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This study aimed to comparatively evaluate the effects of Artemisia annua, isolated artemisinin, and its derivative artemether, administered orally at a dose equivalent to 9.6 mg of artemisinin/kg of feed, in Nile tilapia (Oreochromis niloticus). Two experimental trials were conducted: the first assessed, in vivo, the antioxidant and immunomodulatory effects of the treatments in vaccinated tilapia challenged with Aeromonas hydrophila; the second investigated the antioxidant potential of the treatments on post-slaughter preservation of fillets stored under refrigeration at 4 °C, through physicochemical (pH, colorimetry, and thiobarbituric acid reactive substances – TBARs) and microbiological analyses (coliforms, mesophilic and psychrotrophic microorganisms, Enterobacteriaceae, molds and yeasts, sulfite-reducing Clostridium, and Staphylococcus aureus). Following the cultivation of A. annua, artemisinin and artemether were extracted using HPLC-RI. In the in vivo trial, the experimental groups were: V0 = vaccinated and untreated; V1 = vaccinated and treated with A. annua; V2 = vaccinated and treated with artemisinin; V3 = vaccinated and treated with artemether; NV0 = non-vaccinated and untreated; NV1 = non-vaccinated and treated with A. annua; NV2 = non-vaccinated and treated with artemisinin; NV3 = non-vaccinated and treated with artemether. For the shelf-life study, only non-vaccinated (NV) groups were considered. Supplemented diets were provided for 15 days prior to vaccination (bacterin of A. hydrophila, 1.0×10⁹ CFU/mL, 0.5 mL via intraperitoneal injection), and continued for 15 days to assess the acute inflammatory response (24, 48, and 72 hours post-inoculation). The shelf-life study was conducted after 30 days of dietary supplementation. Results showed that A. annua, artemisinin, and especially artemether positively modulated the immune response of tilapia infected with A. hydrophila, reducing inflammatory cell infiltration, reactive oxygen species (ROS) production, and modulating the acute-phase response, without adverse effects on hepatic or renal parameters. In the shelf-life study, treatments significantly reduced microbial counts (mesophilic, psychrotrophic, Enterobacteriaceae, Staphylococcus spp.) and lipid oxidation levels (TBARs), and attenuated colorimetric changes associated with fillet degradation. Thus, dietary supplementation with A. annua, artemisinin, and artemether enhances the immune response against bacterial infection and contributes to the maintenance of microbiological and physicochemical quality of tilapia fillets during 30 days of refrigerated storage, with the most pronounced effects observed with artemether.

O presente estudo teve por objetivo avaliar comparativamente o efeito de Artemisia annua, do isolado artemisinina e seu derivado artemeter na dose equivalente a 9.6 mg de artemisinina/kg de ração, administrados via oral em tilápias (Oreochromis niloticus). Dois ensaios experimentais foram conduzidos: o primeiro avaliou, in vivo, os efeitos antioxidantes e imunomoduladores dos tratamentos em tilápias vacinadas e desafiadas contra Aeromonas hydrophila; o segundo analisou o potencial antioxidante dos tratamentos sobre a conservação pós-abate de filés refrigerados a 4 °C, por meio de análises físico-químicas (pH, colorimetria e substâncias reativas ao ácido tiobarbitúrico – TBARs) e microbiológicas (coliformes, microrganismos mesófilos e psicrotróficos, Enterobacteriaceae, bolores e leveduras, Clostridium sulfito-redutores e Staphylococcus aureus). Após o cultivo da A. annua, foram realizadas extrações da artemisinina e do artemeter por HPLC-RI. No ensaio in vivo, os grupos experimentais foram: V0 = vacinado e não tratado; V1 = vacinado e tratado com A. annua; V2 = vacinado e tratado com artemisinina; V3 = vacinado e tratado com artemeter; NV0 = não vacinado e não tratado; NV1 = não vacinado e tratado com A. annua; NV2 = não vacinado e tratado com artemisinina; NV3 = não vacinado e tratado com artemeter. Para o estudo de tempo de prateleira, apenas os grupos não vacinados (NV) foram considerados. As dietas suplementadas foram fornecidas por 15 dias antes da vacinação (bacterina de A. hydrophila, 1,0×10⁹ UFC/mL, 0,5 mL via intraperitoneal), e mantidas por mais 15 dias para avaliação da resposta inflamatória aguda (24, 48 e 72 horas pós-inoculação). O experimento de conservação de filés foi conduzido após 30 dias de suplementação. Os resultados demonstraram que A. annua, artemisinina e, principalmente, artemeter modularam positivamente a resposta imune de tilápias infectadas por A. hydrophila, com redução da infiltração celular inflamatória, da produção de espécies reativas de oxigênio (ROS) e modulação da resposta de fase aguda, sem efeitos adversos sobre os parâmetros hepáticos e renais. No estudo de tempo de prateleira, os tratamentos reduziram significativamente as contagens microbianas (mesófilos, psicrotróficos, Enterobacteriaceae, Staphylococcus spp.) e os índices de oxidação lipídica (TBARs), além de atenuarem alterações colorimétricas associadas à degradação dos filés. Assim, conclui-se que a suplementação com A. annua, artemisinina e artemeter melhora a resposta imunológica frente à infecção bacteriana e contribui para a manutenção da qualidade microbiológica e físico-química dos filés de tilápia durante 30 dias de armazenamento refrigerado, com destaque para o artemeter.
Comparative evaluation of the antioxidant activity of Artemisia annua, artemisinin, and artemether administered orally in nile tilapia (Oreochromis niloticus): in vivo and post-harvest studies
Keywords: Ciclídeos; Etnofarmacologia; Aeromonose; Vida útil; Vida útil